Heat Stress on Poultry: Metabolism, Effects and Efforts to Overcome - Tamzil, Mohammad Hasil (Indonesian Bulletin of Animal and Veterinary Sciences, 2014)
Poultry industries in the tropics are challenged by high ambient temperatures and humidities which cause poultry suffer from heat stress. Heat stress contributes to the instability of certain compounds, such as enzymes. Consequently the enzymes function reduces. Affecting the physiological and hormonal conditions of the poultry. In such condition, the body will attempt to restore homeostasis to the state before it happened. When physiological failed to meet the condition, the body will use the genetic pathway by activating Heat Shock Protein (HSP) genes to protect proteins which are sensitive to high temperatures. Heat stress in poultry triggers the emergence of various diseases and affects the growth of poultry and egg production. These negative effects on poultry can be minimized by selecting the type of chickens which are tolerant to high ambient temperature, modifying microclimates of cages and adding anti-stress compounds through feed and or drink. Key words: Heat stress, heat shock protein, physiological conditions, poultry